Social aspects of sustainability of groundnut production in semi arid eastern plains of Rajasthan - J P SINGH; G S BANGARVA; VIKRAM SINGH (The Indian Journal of Agricultural Sciences, 2015)
The importance of sustainability is increasing due to scarce natural resources and growing scientific innovations in agriculture sector. The present study, especially focuses on initiatives, where different social and technical aspects were analyzed on the sustainability of groundnut production in Semi Arid Eastern Plains of Rajasthan, where 200 groundnut producing farmers were identified by using simple random and proportionate sampling methods from Jaipur and Dausa districts of Rajasthan. The results of study revealed that majority of the respondents possessed medium level of knowledge (65.5%) and adoption (68.0%) about sustainable groundnut production. The knowledge level about selection of land and field preparation, improved varieties, sowing, seed rate, seed treatment, irrigation, harvesting and storage was high in order, while it was comparatively low in case of fertilizer application and plant protection measures. Whereas, aspect wise adoption level of seed rate, improved varieties, seed treatment, irrigation, spacing, weed control, harvesting and storage was comparatively high. It was low in case of fertilizer application and plant protection measures about sustainable groundnut production. The correlation analysis revealed that the social aspects, viz. land holding, socio economic status, education, family education, economic motivation, source of information utilized, change proneness and attitude towards sustainable groundnut production having significant positive relationship with knowledge and adoption level of sustainable groundnut production.